Tingkat Kecemasan Keluarga Komorbid Saat Pandemi COVID-19 di Kelurahan Grendeng Purwokerto Utara - Pratama, Koernia Nanda; Triyanto, Endang; Kartikasari, Aprilia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Background: The current condition, namely the New Normal Era during the COVID-19 pandemic, requirespeople to follow the COVID-19 protocol according to the appeal from the government. The externalities ofCOVID-19 greatly impact psychological problems (anxiety) in vulnerable communities. Therefore, thefamily has the duty of Health in maintaining the health of comorbid family members. Efforts that can bedone are to make preventive efforts in families with comorbid diseases as a risk factor for death due toCOVID-19. Purpose: This study was to describe the level of anxiety of the comorbid family in GrendengVillage, North Purwokerto. Methods: This research is an observational study with a cross sectionalapproach. The sample of this study was 200 heads of families with comorbid diseases in Grendeng Village,North Purwokerto which were selected by total sampling. The implementation of health tasks is measuredusing an instrument. Anxiety was measured using the modified HARS (Hamilton Anxiety Rating Scales).Data analysis using non-parametric Spearman. Results: the survey results showed that the variable level ofmild anxiety was 50%, 39.5% of comorbid families had no anxiety, and 10.5% of families with moderateanxiety level, and none had severe or very severe anxiety. Conclusion: comorbid families in the GrendengVillage area need to apply the Covid19 protocol well even though they are able to control the anxiety rate.